Detection of Enterotoxigenic Clostridium perfringens in Meat Samples by Using Molecular Methods - Kaneko, Ikuko (American Society for Microbiology, 2011)
To prevent food-borne bacterial diseases and to trace bacterial contamination events to foods, microbial source tracking (MST) methods provide important epidemiological information. To apply molecular methods to MST, it is necessary not only to amplify bacterial cells to detection limit levels but also to prepare DNA with reduced inhibitory compounds and contamination. Isolates carrying the Clostridium perfringens enterotoxin gene (cpe) on the chromosome or a plasmid rank among the most important food-borne pathogens. Previous surveys indicated that cpe-positive C. perfringens isolates are present in only ∼5% of nonoutbreak food samples and then only at low numbers, usually less than 3 cells/g. In this study, four molecular assays for the detection of cpe-positive C. perfringens isolates, i.e., ordinary PCR, nested PCR, real-time PCR, and loop-mediated isothermal amplification (LAMP), were developed and evaluated for their reliability using purified DNA. For use in the artificial contamination of meat samples, DNA templates were prepared by three different commercial DNA preparation kits. The four molecular assays always detected cpe when >10(3) cells/g of cpe-positive C. perfringens were present, using any kit. Of three tested commercial DNA preparation kits, the InstaGene matrix kit appeared to be most suitable for the testing of a large number of samples. By using the InstaGene matrix kit, the four molecular assays efficiently detected cpe using DNA prepared from enrichment culture specimens of meat samples contaminated with low numbers of cpe-positive C. perfringens vegetative cells or spores. Overall, the current study developed molecular assay protocols for MST to detect the contamination of foods with low numbers of cells, and at a low frequency, of cpe-positive C. perfringens isolates.